2020
DOI: 10.1101/2020.07.23.218727
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decreasing alertness modulates perceptual decision-making

Abstract: The ability to make decisions based on external information, prior knowledge and context is a crucial aspect of cognition and it may determine the success and survival of an organism. Despite extensive and detailed work done on the decision making mechanisms, the understanding of the effects of arousal remain limited. Here we characterise behavioural and neural dynamics of decision making in awake and low alertness periods to characterise the compensatory signatures of the cognitive system when arousal decreas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 96 publications
0
8
0
Order By: Relevance
“…Some weak evidence against a premotor explanation of detected differences comes from the observation of scalp distribution of decoder weights (Figure S5) and RTs (Table S2). Particularly, in graphs C and D of Figure S5, it is noticeable how the spatial patterns generating later peaks of performance are not homogeneous across time, and they do not overlap with the expected distribution underlying motor preparation or planning (Jagannathan et al, 2021). However, it is important to keep in mind that the small sample size and the suboptimal nature of our task (from a cortical differentiation perspective) may have heavily hindered the reliability of these spatial clustering results.…”
Section: Discussionmentioning
confidence: 96%
“…Some weak evidence against a premotor explanation of detected differences comes from the observation of scalp distribution of decoder weights (Figure S5) and RTs (Table S2). Particularly, in graphs C and D of Figure S5, it is noticeable how the spatial patterns generating later peaks of performance are not homogeneous across time, and they do not overlap with the expected distribution underlying motor preparation or planning (Jagannathan et al, 2021). However, it is important to keep in mind that the small sample size and the suboptimal nature of our task (from a cortical differentiation perspective) may have heavily hindered the reliability of these spatial clustering results.…”
Section: Discussionmentioning
confidence: 96%
“…The increased volatility in the PRL with low arousal suggests a decrease in cognitive control that is different from an increase in perseverative behaviour seen in high arousal. Indeed, we have previously shown that decreased levels of arousal can fragment or reconfigure specific aspects of cognition while preserving crucial executive control processes such as the capacity to detect and react to incongruity, 18 the efficiency in perceptual decision making, 31 and the precision of conscious access. 17 Here, we add further evidence showing that individuals under reduced arousal state, although struggling to maintain stable evidence-based decision-making patterns, are able to learn new S-R reinforcement contingencies, demonstrating flexibility of the human brain to adapt to increasing levels of endogenous (arousal) noise.…”
Section: The Fragmentation Of Cognitive Control Due To Changes In Arousal Has Been Primarilymentioning
confidence: 99%
“…Based on the premises that (1) drowsiness hinders the extraction of task-relevant information from external stimuli and its integration, fragmenting specific aspects of cognition while preserving crucial executive control processes; 18,31,33,41 (2) drowsiness has been associated with more liberal decision-making; 17,30,31 (3) moderate-to-high intensity endurance exercise leads to a selective enhancement of executive control processes while lower and higher intensities result in an impairment or minimal effect; 40,42,43 and (4) high arousal promotes habitual responding and reduced engagement of complex cognitive strategies; 44,45,46 we predicted that behavioural performance would be enhanced in moderate-intensity physical exercise, while drowsiness and high-intensity exercise would lead to diminished performance in light of the inverted U-shaped Yerkes-Dodson Law. Specifically, we hypothesized that reduced arousal states would be associated with an impairment of performance (compared to baseline), which would be attributed to a tendency to apply a simple strategy (win-stay/loseshift) instead of using an integrated history of choices and outcomes to drive performance (probabilistic switching behaviour).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the premises that (1) drowsiness hinders the extraction of task-relevant information from external stimuli and its integration, fragmenting specific aspects of cognition while preserving crucial executive control processes; 18,31,33,41 (2) drowsiness has been associated with more liberal decision-making; 17,30,31 (3) moderate-to-high intensity endurance exercise leads to a selective enhancement of executive control processes while lower and higher intensities result in an impairment or minimal effect; 40,42,43 and (4) high arousal promotes habitual responding and reduced engagement of complex cognitive strategies; 44,45,46 we predicted that behavioural performance would be enhanced in moderate-intensity physical exercise, while drowsiness and high-intensity exercise would lead to diminished performance in light of the inverted U-shaped Yerkes-Dodson Law. Specifically, we hypothesized that reduced arousal states would be associated with an impairment of performance (compared to baseline), which would be attributed to a tendency to apply a simple strategy (win-stay/lose-shift) instead of using an integrated history of choices and outcomes to drive performance (probabilistic switching behaviour).…”
Section: Introductionmentioning
confidence: 99%
“…,27,28, 29 Drowsiness, as well as similar reduced arousal states, has been repeatedly associated with an impairment of cognitive processing, and particularly the capacity to deal with conflicting information, 18 attentional performance, 30 and perceptual decision-making. 31 However, in drowsiness, and even during highly reduced arousal states, pre-attentive and early bottom-up attentive processing can still be accomplished with and without conscious awareness. 17,32,33 The transition towards the other side of the arousal spectrum (i.e., heightened arousal states) has received even less attention.…”
Section: Introductionmentioning
confidence: 99%